Laplacian SVM for Learning from Label Proportions - Limeng Cui; Zhensong Chen; Fan Meng; Yong Shi (IEEE ... International Conference on Data Mining workshops, 2016)
Proportion-SVM has been deeply studied due to its broad application prospects, such as modeling voting behaviors and spam filtering. However, the geometric information has been widely ignored. Thus, current methods usually show sensitivity to noises. To address these problems, in this paper, we combine the proportion learning framework with Laplacian term. We exploit the advantages of Laplacian term. Extensive experiments show the effectiveness of our method.